Using the zebrafish to understand tendon development and repair - Chen, Jessica W. (Methods Cell Biol, 2016)
Tendons are important components of our musculoskeletal system. Injuries to these tissues are very common, resulting from occupational-related injuries, sports-related trauma, and age-related degeneration. Unfortunately, there are few treatment options, and current therapies rarely restore injured tendons to their original function. An improved understanding of the pathways regulating their development and repair would have significant impact in stimulating the formulation of regenerative-based approaches for tendon injury. The zebrafish provides an ideal system in which to perform genetic and chemical screens to identify new pathways involved in tendon biology. Until recently, there had been few descriptions of tendons and ligaments in the zebrafish and their similarity to mammalian tendon tissues. In this chapter, we describe the development of the zebrafish tendon and ligament tissues in the context of their gene expression, structure, and interactions with neighboring musculoskeletal tissues. We highlight the similarities with tendon development in higher vertebrates, showing that the craniofacial tendons and ligaments in zebrafish morphologically, molecularly, and structurally resemble mammalian tendons and ligaments from embryonic to adult stages. We detail methods for fluorescent in situ hybridization and immunohistochemistry as an assay to examine morphological changes in the zebrafish musculoskeleton. Staining assays such as these could provide the foundation for screen-based approaches to identify new regulators of tendon development, morphogenesis, and repair. These discoveries would provide new targets and pathways to study in the context of regenerative medicine-based approaches to improve tendon healing.